Emperical Oral Antibiotic Therapy for Children with Low Risk Febrile Neutropenia during Cancer Chemotherapy - Shrestha, PN; Sah, K; Rana, R (Journal of Nepal Paediatric Society, 2009)
Introduction: In patient with fever and neutropenia during cancer chemotherapy who have a low risk of complications, oral antibiotic may be an acceptable alternative to intravenous antibiotics. Methods: We conducted a prospective hospital based study to the patients who had fever and neutropenia during caner chemotherapy. Only low risk patients i.e. neutropenia of less than seven days, ANC >250/cmm, without any signs of shock were included in the study. All the patients were hospitalized and given oral antibiotics Ofloxacin and Amoxy-Clav and were closely observed until fever subsided for more than 48 hours and improved from neutropenia. Results: A total of 54 cases were enrolled in the study. Out of 54 patients two patients were lost, 8 needed IV antibiotics for different reasons and 44 patients (81%) improved well with oral antibiotics only. Conclusion: In hospitalized low risk patients who have fever and neutropenia, empirical therapy with oral ofloxacin and amoxy-clav may be a safe alternative to IV antibiotics. Key words: Febrile Neutropenia, Cancer Chemotherapy, ANC. doi:10.3126/jnps.v29i1.1596 J. Nepal Paediatr. Soc. Vol.29(1) p.22-25